Thermal conductivity properties of graphene based epoxy nanocomposite - Raja N Othman,; Muhammad S. Zainordin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Thermally conductive polymer composites offer new potentials for replacing metal parts in numerous applications, including power electronics, electric motors and generators, heat exchangers, and so on. Current interest to enhance the thermal conductivity of polymers is focused on the selective addition of nanofillers with high thermal conductivity. Therefore, graphene is the best choice material for thermally conductive composite. This study focuses on conducting the experiment to measure the thermal conductivity of graphene based epoxy nanocomposites with various variables and preparation conditions. Along this project, a series of experiment is done by manipulating the graphene loading ratio, the stirring rate, and the stirring time. 34 samples were prepared, tested, and analysed in order to determine the composite samples with the optimum variables. At the end of the experiment, the highest thermal conductivity of graphene based epoxy nanocomposites is identified at 0.204 W/mK. The optimum variables and conditions that came out with the best result are 0.3 wt% of graphene loading and 500 rpm of stirring rate at 30 minutes of stirring time. The enhancement of the thermal conductivity is 19.53% higher than that of the neat epoxy alone which is 0.17067 W/mK. This project is expected to serve as a good reference for future studies.